Worm Catchers: an Experience of Social Appropriation of Knowledge in Cienaga, magdalena (2018)
Researcher Maria Adelaide for her interest in the tropics and diseases caused by the trichocephalic parasite arrives in Ciénaga, Magdalena accompanied by a research group from the University of Antioquia with the interest of doing a community awareness work, through comics in which children could be reflected and thus want to collaborate with the studies.